2020
DOI: 10.1155/2020/5219367
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Optic Nerve Sheath Diameter for Neurological Outcomes in Post‐Cardiac Arrest Patients: A Systematic Review and Meta‐Analysis

Abstract: Objective. The present study investigated whether optic nerve sheath diameter (ONSD) could be used to predict neurological outcomes in post-cardiac arrest (CA) patients. Methods. We performed a comprehensive literature search in the Cochrane Library, ScienceDirect, PubMed, and Web of Science from inception to June 2020 for eligible articles. Stata 14.0 software was used to calculate the pooled odds ratios (ORs) and 95% confidence intervals (95% CIs), sensitivity, specificity, summary receiver operating charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In the analysis of ONSD as a predictor of neurological outcomes, the overall ONSD was found to be higher in the PNO group than in the GNO group (SMD = 0.74; 95% CI = 0.22–1.27; I 2 = 87%). However, unlike previous systematic reviews that showed usefulness in predicting neurological prognosis of ONSD [ 7 , 8 ], it is difficult to determine whether an enlarged ONSD is useful for the prediction of neurological outcomes in PCAS. This is because after separating the neurological outcome by the measurement interval, we found that the results were different depending on the measurement time and that the low heterogeneity of outcomes (1 month and in-hospital mortality) was not feasible to draw a conclusion, owing to the lack of studies and low quality of evidence according to GRADE level.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the analysis of ONSD as a predictor of neurological outcomes, the overall ONSD was found to be higher in the PNO group than in the GNO group (SMD = 0.74; 95% CI = 0.22–1.27; I 2 = 87%). However, unlike previous systematic reviews that showed usefulness in predicting neurological prognosis of ONSD [ 7 , 8 ], it is difficult to determine whether an enlarged ONSD is useful for the prediction of neurological outcomes in PCAS. This is because after separating the neurological outcome by the measurement interval, we found that the results were different depending on the measurement time and that the low heterogeneity of outcomes (1 month and in-hospital mortality) was not feasible to draw a conclusion, owing to the lack of studies and low quality of evidence according to GRADE level.…”
Section: Discussionmentioning
confidence: 97%
“…Using ocular US and brain CT, two recent systematic reviews demonstrated that ONSD had a high diagnostic value for predicting poor neurological outcomes (PNO) in patients with PCAS [ 7 , 8 ]. In these reviews, ONSD showed low pooled sensitivity, high pooled specificity, and high area under the receiver-operating characteristic curve.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have applied the ONSD in combination with other predictors, including GWR and albumin levels, to enhance the predictive value [ 13 , 19 , 21 ]. Moreover, two recent meta-analyses reported the potential use of the ONSD in predicting neurologic outcomes [ 19 , 20 ]. A registry-based multicenter study demonstrated inconsistency with these previous findings, as it reported no correlation between the ONSD on early unenhanced brain CT and neurologic outcomes in post-CA survivors managed with TTM administration [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent studies have demonstrated that the ONSD on brain CT is useful for early neurologic outcome prediction through the evaluation of increased ICP in patients with post-CA ROSC [14,18]. Two recent meta-analyses confirmed the utility of the ONSD as a prognostic factor for neurologic outcomes in post-CA patients [19,20]. However, the methodology of these systematic reviews and meta-analyses is concerning [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation